The coronavirus disease (COVID-19) pandemic: we urgently need to look beyond the virus - Mena, María Belén (2020)
The conception of health as the provision of hospital services, medical treatment, prescription, and delivery of drugs to treat illness is a narrow and fragmented conception of the right to health. It is not the SARS-CoV-2 of just 20 nanometers that is hitting our fragile health systems; it is the breakdown of the social balance and the weak impact of the ecosystemic approach to social determinants of health in dealing with this pandemic.